Associations Between Infant Developmental Delays and Secondhand Smoke Exposure Modified by Maternal Prepregnancy Overweight and Obesity Status. Issue 9 (8th February 2021) - Wei, Chih-Fu; Lin, Ching-Chun; Tsai, Meng-Shan; Guo, Yueliang Leon; Lin, Shio-Jean; Liao, Hua-Fang; Hsieh, Wu-Shiun; Chen, Mei-Huei; Chen, Pau-Chung
Abstract: Introduction: Secondhand smoke exposure during pregnancy has long been associated with adverse health outcomes in children, but only a few studies have examined its effect modifiers. In this study, we applied effect modification analysis for maternal prepregnancy weight status on detrimental neurodevelopmental effect of secondhand smoke exposure during pregnancy and infancy in a nationwide representative population. Aims and Methods: Term singleton mother–infant pairs with nonsmoking mothers were included for main analysis ( N = 15 987) from the Taiwan Birth Cohort Study (TBCS), and were further matched with propensity score ( n = 5434). We extracted secondhand smoke exposure during pregnancy and infancy, and eight neurodevelopmental milestones from the responses in the baseline visit at 6 months, and 18-month follow-up of TBCS. The associations between secondhand smoke exposure and neurodevelopmental achievement were analyzed with multivariable logistic regression and Cox model. Propensity score weighting and matching were applied for high-versus-low analysis, and relative excess risk due to interaction were used to estimate effect modification. Results: Higher secondhand smoke exposure was associated with increased likelihood of delayed milestone achievement across gross motor, fine motor, language-related, and social-related domains. The associations in fine motor domains remained observable in propensity score-weighted and -matched models. We identified additive interaction with self-reported maternal overweight and obesity status before pregnancy in milestone development for walking with support, scribbling, and waving goodbye. Conclusions: Secondhand smoke exposure during pregnancy and infancy were associated with delayed neurodevelopmental milestone achievement at 18 months, and the associations were modified by maternal prepregnancy overweight and obesity status. Implications: The study results suggested the association between maternal secondhand smoke exposure during pregnancy and infancy and delayed fine motor and language-related milestone achievement at 18 months in multivariable, propensity score weighting, and matching populations. The results of positive effect modifications for maternal prepregnancy overweight and obesity status suggested the importance of concurrent interventions on smoke-free environment and maternal health during pregnancy.